The Seismotectonic Significance of Geofluids in Italy - Vannoli, Paola; Martinelli, Giovanni; Valensise, Gianluca (Frontiers in Earth Science, 2021)
One of the growing topics in the Earth Sciences is the understanding of how geofluid emissions are released in the atmosphere by the planet’s geodynamic activity, and how much they contribute to the global budget of greenhouse gases. Many workers are facing this issue with studies conducted at global scale, so as to get the required global-scale answers. The data available at the global scale on geofluids, faults, earthquakes and volcanoes, however, are generally too coarse to provide these answers. We investigate the relationships between geofluid emissions and tectonics at a more detailed scale. Standing on over a century of data on geofluid emissions and on an extensive knowledge of the region’s tectonics and seismicity, we focused on Italy, one of the regions of the globe that experience the largest release of natural CO2 and CH4. We systematically overlaid and compared data collected by a number of workers into 13 published countrywide databases concerning geofluids, carbon-bearing deposits, seismogenic faults, historical and instrumental earthquakes, and heat flow observations. Our results indicate that (a) thermal springs and CO2 emissions dominate in areas of mantle upwelling and crustal stretching, but also that (b) some of them occur in the extending inner Apennines, generally along major lithospheric chain-perpendicular lineaments that bound the largest normal faults. Conversely, (c) CH4 emissions and mud volcanoes dominate in areas undergoing active contraction, where no CO2 emissions are observed; in particular, (d) mud volcanoes fall where the crest of active anticlines intersects major lithospheric chain-perpendicular lineaments. An overarching conclusion is that in Italy the release of geofluids is primarily controlled by deep crustal discontinuities that developed over the course of 5-10 My, and is only mildly affected by the ongoing crustal strains. The geofluids bring information on processes that occur primarily in the lower crust, marking the surface projection of generally hidden discontinuities that control the geometry and modes of seismic release. As such they may also provide valuable insight for improving the assessment of seismic hazard in hard-to-investigate active regions, such as Italy.